Morphological responses of root hairs to changes in soil and climate depend on plant life form - Zhou, Yingtong; Wang, Cunguo; Tang, Qinrong; Wang, Junni; Li, Mai-He (Frontiers in Forests and Global Change, 2024)
Root hairs increase the surface area of a plant’s root system that is in contact with the soil, thus facilitating plant water and nutrient uptake. However, little is known about the characteristics of the root hairs of herbaceous and woody plants and their specific response patterns to biotic and abiotic variables from the perspective of resource acquisition strategies in the context of global change. Here, we analyzed 74 published case studies with 1074 observations of root hair traits to identify patterns of root hair length, density and diameter in relation to soil (e.g., soil pH, nutrient levels), growing environments (e.g., greenhouse, field) and climatic factors (e.g., air temperature), as well as genome size and plant age Root hairs were longer, denser and thicker in woody plants compared with herbaceous plants, and the length and diameter of root hairs in herbaceous plants increased with genome size. With increasing plant age, woody plants had significantly longer and thicker root hairs, while root hair density and diameter declined significantly for herbaceous plants. Soil-cultured plants had longer root hairs than solution-cultured plants. The length and density of root hairs were greater in greenhouse-cultured plants than in field-grown plants, and the latter had thicker root hairs than the former. As soil pH increased, root hair length increased but diameter decreased in woody plants, while root hair density increased in herbaceous plants. Increased soil total nitrogen (N) and potassium (K) significantly increased root hair length, density and diameter in herbaceous plants, while soil total N significantly decreased root hair density in woody plants. Root hair length increased significantly, while root hair density decreased significantly, with higher mean annual temperature and greater precipitation seasonality, while the opposite pattern was true for a wider annual temperature range. Our findings emphasize the life-form-specific responses of root hairs to soil and climatic variables. These findings will help deepen our understanding of resource acquisition strategies and their mechanisms in different plant forms under global climate change.